Effects of porous material and nanoparticles on the thermal performance of a flat plate solar collector: An experimental study. (December 2017) - Jouybari, H. Javaniyan; Saedodin, S.; Zamzamian, A.; Nimvari, M. Eshagh; Wongwises, S.
Abstract: The thermal performance of a nanofluid flow through a flat plate solar collector with the metal porous foam filled channel is experimentally investigated. For this purpose, the SiO2 /deionized water nanofluids are prepared with volume fractions of 0.2%, 0.4% and 0.6% then their thermal behavior is examined on the porous channel collector based on the ASHRAE standard. Based on the experimental results, the thermal efficiency is improved up to 8.1% in the nanofluid flow. Using the porous media and nanofluid causes an undesirable increase in the pressure drop. To take both the heat transfer enhancement and pressure drop into consideration, a Performance Evaluation Criterion ( PEC ) has been used for nanofluid and porous media, separately. It is observed that as the nanoparticle volume fraction increases from 0.2% to 0.6%, the performance of nanofluid flow, PEC n f, is enhanced from 1.07 to 1.34 in the lowest flow rate (0.5 lit / min ) . Also, the performance evaluation of the porous media, PEC p, shows that the solar collector performance is improved up to 0.92 with increasing the nanofluid concentration and reduction of the flow rate. Finally, the effects of SiO2 nanoparticle size, i.e. 7 nm, 20–30 nm and 60–70 nm, have been investigated on the collector thermal performance. Results show that the efficiency curve slope parameter decreases with diminishing the nanoparticle size. Highlights: Thermal performance of a porous channel FPSC with nanofluid flow has been studied. SiO2 nanofluid despite low thermal conductivity has a great effect on efficiency. Greater values of flow rates are more effective at lower reduced temperature. Variation of nanofluid performance (PEC) versus flow rate has a decreasing trend. Removed energy parameter is directly proportional to the nanopaticle size.